Analysis of Factors Affecting the Value of Local Government Financial Reporting Information - Okta Sandria; Elfiswandi; Yamasitha (UPI YPTK Journal of Business and Economics, 2021)
This study aims to analyze the effect of the quality of human resources on the reliability and timeliness of local government financial reporting in Suliki sub-district and the effect of information technology utilization variables on the reliability and timeliness of local government financial reporting in Suliki sub-district. The data used in this study is primary data consisting of 46 samples. This research uses Multiple Linear Regression Analysis method. The results of the analysis show that the variable quality of human resources has a positive significant relationship to the reliability and timeliness of local government financial reporting in Suliki district, the variable of information technology utilization has a positive significant relationship to the reliability and timeliness of local government financial reporting in Suliki district and simultaneously variable independent has a significant positive effect on the dependent variable. This can be seen from the coefficients of each variable and the level of significance.